Proyecto de diseño de un sistema de sensores inerciales de bajo costo que capturan datos cinemáticos en espacio no controlado para el apoyo al diagnóstico o monitoreo de rehabilitación en pacientes con discapacidad en extremidades inferiores (2020)
Starting with the experience of a member of the DOCSA SENSORS team, who had a traumatic rehabilitation process after a cruciate ligament tear and countless visits to the specialist and to movement analysis laboratories. A need arises to provide patients with not only torn ligaments but also Parkinson's, hydrocephalus and even high-performance athletes access to quick and easy diagnosis or monitoring of gait. It is not intended to completely replace a motion analysis laboratory, but if there is a significant number of patients that with an examination that provides kinematic data to the medical professional, they can be diagnosed and or monitored without the need to attend a complex laboratory motion analysis. Thus, the need and mission of DOCSA SENSORS is to develop a way to collect kinematic data in uncontrolled space for support in the diagnosis or monitoring of rehabilitation in patients with disabilities in the lower extremities.